Access to credit, education and entrepreneurial competencies: a study among women micro-entrepreneurs in Malaysia - Abdullah Al- Mamun (SAGE Publications, 2016)
This study examines how entrepreneurial competencies, education and total amount of credit received affect the performance of microenterprises owned and managed by Amanah Ikhtiar Malaysia’s (AIM) successful women micro-entrepreneurs in Malaysia. This study, using a cross-sectional design, collected quantitative data from 407 women micro-entrepreneurs through structured interviews. Findings of this study indicate that women micro-entrepreneurs’ level of education, entrepreneurial competencies and total amount of economic credit received have a significant positive effect on microenterprise performance. Among these three aspects, credit received has a relatively higher effect on microenterprise performance followed by level of education and entrepreneurial competencies. Therefore, AIM should focus on designing a flexible and diversified credit programme, followed by specialized training programmes, and facilitate sharing of experiences in order to improve the competencies, which could ultimately improve the performance of microenterprises owned and managed by the low-income women micro-entrepreneurs in Malaysia.